Haplotype analysis of the folate-related genes MTHFR, MTRR, and MTR and migraine with aura. (May 2013) - Roecklein, Kathryn A; Scher, Ann I; Smith, Albert; Harris, Tamara; Eiriksdottir, Gudny; Garcia, Melissa; Gudnason, Villi; Launer, Lenore J
Aims: The C677T variant in the methylenetetrahydrofolate reductase ( MTHFR ; EC 1.5.1.20) enzyme, a key player in the folate metabolic pathway, has been associated with increased risk of migraine with aura. Other genes encoding molecular components of this pathway include methionine synthase ( MTR ; EC 2.1.1.13) and methionine synthase reductase ( MTRR ; EC 2.1.1.135) among others. We performed a haplotype analysis of migraine risk and MTHFR, MTR, and MTRR . Methods: Study participants are from a random sub-sample participating in the population-based AGES-Reykjavik Study, including subjects with non-migraine headache ( n  = 367), migraine without aura ( n  = 85), migraine with aura ( n  = 167), and no headache ( n  = 1347). Haplotypes spanning each gene were constructed using Haploview. Association testing was performed on single SNP and haplotypes using logistic regression, controlling for demographic and cardiovascular risk factors and correcting for multiple testing. Results: Haplotype analysis suggested an association between MTRR haplotypes and reduced risk of migraine with aura. All other associations were not significant after correcting for multiple testing. Conclusions: These results suggest that MTRR variants may protect against migraine with aura in an older population.